ANALISIS FINANSIAL JANGKA PENDEK USAHA KAPAL IKAN DI KABUPATEN KARIMUN - Muhammad hadi (Fakultas Sains dan Teknologi Universitas Karimun, 2021)
Fishing by fishermen in the process is assisted by fishing tools. this tool is a fishing boat. Hereditary fishing boats have been made for use by fishermen to get fish, the increase in demand for fishing boat production will increase along with the growth of coastal communities. Karimun is one of the areas where the majority of the population works as fishermen, with this potential supporting the birth of local fishing boat producers. Local fishing boat producers are able to compete with good quality, with this potential this research was conducted to analyze the feasibility of fishing boat business in Pasuruan district with a short-term analysis which resulted in R / C value and profitability of fishing boat business in Karimun respectively 1.686 and 168.55% per year. The results obtained are more than the eligibility limit, so the wooden boatyard business in Karimun meets the feasibility value index to continue and develop the business.